Indexes for motor performance assessment in job integration/reintegration of people with neuromuscular disorders: A systematic review - Chini, Giorgia; Fiori, Lorenzo; Tatarelli, Antonella; Varrecchia, Tiwana; Draicchio, Francesco; Ranavolo, Alberto (Frontiers in Neurology, 2022)
Patients of working age affected by neuromuscular disorders often have problems related to employability, difficulties in working, and premature work interruption. Anyway, targeted rehabilitation as well as ergonomic and training interventions can allow them to return-to-work. Biomechanical and physiological indexes are useful for motor and muscles performance monitoring and to verify the effectiveness of the interventions for job integration. Therefore, it is necessary to evaluate which indexes present in the literature are the most appropriate to evaluate the effectiveness and efficiency of the return-to-work programs. To achieve this goal this paper uses a systematic literature review methodology (selecting articles published from 2011 until 30 March 2021 from Scopus, Web of Science and PubMed checking the eligibility and the potential risk of bias) to review recent scientific bibliography and to identify current and future valuable indexes. The most used indices for motor performance assessment were identified, categorized, and analyzed. From this review emerged an enormous potential of kinetic, kinematic, surface electromyography, postural and other Biomechanical and physiological indexes. These indexes can be calculated for work-task and workplace rehabilitation to design patient-specific interventions by using sensor networks, machine learning algorithms and intelligent work environments also to enable direct feedback to workers.